2012
DOI: 10.1016/j.oooo.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cone-beam computed tomography incidental findings between patients with moderate/severe obstructive sleep apnea and mild obstructive sleep apnea/healthy patients

Abstract: Objective To compare the incidental radiographic findings in the maxillofacial structures and the pharyngeal airway between moderate/severe Obstructive Sleep Apnea (OSA) subjects and mild OSA/normal subjects using Cone-Beam Computed Tomography (CBCT) scans. Study Design 53 moderate/severe OSA subjects (with a Respiratory Disturbance Index [RDI]≥15 events/hr) and 33 mild OSA/normal subjects, (RDI<15) based on ambulatory somnographic assessment were recruited. Supine CBCT’s were taken and sent for radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 38 publications
0
18
0
3
Order By: Relevance
“…This finding has a relevant implication in clinical practice. In fact, considering that especially in severe OSAS, the clinicians are accustomed to using an additional radiological examination (teleradiography in lateral projection or CT) to better evaluate the signs of the syndrome, 20,21 it confirms that an X-ray-free examination (which is MRI) can effectively replace traditional radiography or CT. Moreover, clinicians should consider that since adenotonsillar hypertrophy constitutes the most related element to sleep apnoea syndrome in children and that other soft-tissue and skeletal tissue structures could influence the symptoms and their severity, 19 the use of an auxiliary examination would be able to accurately define such tissue dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding has a relevant implication in clinical practice. In fact, considering that especially in severe OSAS, the clinicians are accustomed to using an additional radiological examination (teleradiography in lateral projection or CT) to better evaluate the signs of the syndrome, 20,21 it confirms that an X-ray-free examination (which is MRI) can effectively replace traditional radiography or CT. Moreover, clinicians should consider that since adenotonsillar hypertrophy constitutes the most related element to sleep apnoea syndrome in children and that other soft-tissue and skeletal tissue structures could influence the symptoms and their severity, 19 the use of an auxiliary examination would be able to accurately define such tissue dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In the aetiology of OSA, some of the most important parameters are the airway volume, airway length and various anthropometric measurements [1,9,10,21,36]. According to the CT study performed by Enciso et al [10], men older than 57 years and individuals having narrow upper airway measurement have been identified as a high risk group for OSA. Mayer et al [21] has also reported an increase in the width of the oropharynx in OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mayer et al [21] has also reported an increase in the width of the oropharynx in OSA patients. The long and narrow airway had increased the frequency of airway collapse [10,21,36].…”
Section: Discussionmentioning
confidence: 99%
“…11) Others: CBCT is accurate in predicting bone involvement in malignancies and is comparable to CT and single-photon emission CT (SPECT). 36) CBCT has also been reported to be of value in the detection of accessory foramina in the mandible, 37,38) osteomyelitis in combination with scintigraphy, 39) osteomalacia, 40) salivary calculus, 41) the diagnosis and treatment planning of clinically present sinusitis, 42) the identification of maxillofacial and airway anomalies that could interfere with normal breathing, 43) in image-guided surgeries, 44) in predicting post-operative results in mid-face fractures, 45) and in assessing pterygoid hamulus morphology. 46)…”
Section: T Okano and Othersmentioning
confidence: 99%